2022
DOI: 10.1111/mcn.13397
|View full text |Cite
|
Sign up to set email alerts
|

Healthier diet associated with reduced risk of excessive gestational weight gain: A Chinese prospective cohort study

Abstract: Limited studies have examined the associations between diet quality and gestational weight gain (GWG) among Chinese pregnant women, adopting Chinese GWG guidelines. We prospectively investigate the associations of diet quality, using the Chinese Healthy Diet Index for Pregnancy (CHDI-P), which assessed diet quality from 'Diversity', 'Adequacy' and 'Limitation' dimensions with overall 100 points, with GWG among participants enroled in Southwest China. Food consumption was collected by 24 h dietary recalls for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…It was developed from evidence linking various food components with maternal health, as established through large-scale population studies and encompasses 23 food components. The validity of CHDI-P was confirmed in a cohort study involving 1,416 Chinese pregnant women ( Yang et al, 2023 ). The CHDI-P scale provides a comprehensive three-dimensional evaluation of dietary quality.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…It was developed from evidence linking various food components with maternal health, as established through large-scale population studies and encompasses 23 food components. The validity of CHDI-P was confirmed in a cohort study involving 1,416 Chinese pregnant women ( Yang et al, 2023 ). The CHDI-P scale provides a comprehensive three-dimensional evaluation of dietary quality.…”
Section: Methodsmentioning
confidence: 83%
“…We assessed the dietary quality of expectant mothers using the Chinese Healthy Dietary Index for Pregnancy (CHDI-P) ( Yang et al, 2023 ). The CHDI-P scale is derived from the 2016 edition of the Dietary Guidelines for Pregnant Women in China ( Yang et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of this special collection of papers is to bring together research that has been conducted on GWG in China. These papers (Song et al, 2023 ; Wang et al, 2023 ; Yang et al, 2023 ) provide new local evidence that may be used for developing global GWG guidelines.…”
mentioning
confidence: 99%
“…In the third paper of this section, Yang et al ( 2023 ) describe the relationship between diet quality and excessive GWG from a prospective cohort study (Yang et al, 2023 ). The study showed that higher diet quality during the second and third trimesters was associated with lower odds of excessive GWG for both normal weight and overweight women.…”
mentioning
confidence: 99%
See 1 more Smart Citation